Simplified Method for Single Line to Ground-Fault Location in Electrical Power Distribution Systems - Mustapha Zahri; Youssef Menchafou; Hassane El Markhi; Mohamed Habibi (Institute of Advanced Engineering and Science, 2015)
Power distribution systems play important roles in modern society. When distribution system outages occur, speedy and precise fault location is crucial in accelerating system restoration, reducing outage time and significantly improving system reliability, and then improves the quality of services and customer satisfaction. In this paper, we propose a reduced algorithm utilizing the sum of sending-end currents of the three phases to calculate the fault current, and therefore, avoid the iterative aspect of the classic algorithm for single line to ground fault location and reduce its computational charge. The test results are obtained from the numerical simulation using the data of a distribution line recognized in the literature.